Summary of head-to-head comparisons of patient risk classifications by the 21-gene Recurrence Score® (RS) assay and other genomic assays for early breast cancer - Varga, Zsuzsanna; Sinn, Peter; Seidman, Andrew D. (International journal of cancer, 2019)
Many genomic assays that assess recurrence risk in early breast cancer (EBC) are prognostic, but they differ in risk group stratification, which can affect clinical utility. Prospective outcomes of >60 K patients treated based on the 21-gene assay results have shown that chemotherapy may be safely omitted in EBC patents with low Recurrence Score (RS) results (RS < 18). Because of its extensive validation and wide clinical use, the RS assay is a common comparator in head-to-head studies with other assays. Published/presented studies of the RS assay performed on the same tumor samples with Breast Cancer Index (BCI), EndoPredict (EP) or EP+ clinical features (EPclin), MammaPrint (MMP) and/or Prosigna (ROR) assays were reviewed. Study findings were summarized descriptively.
Gesehen am 16.07.2019